Outsourcing Security : Private Military Contractors and U.S. Foreign Policy - Stanley, Bruce E. (Bruce Edwin) (Book collections on Project MUSE., 2015)
Faced with a decreasing supply of national troops, dwindling defense budgets, and the ever-rising demand for boots on the ground in global conflicts and humanitarian emergencies, decision makers are left with little choice but to legalize and legitimize the use of private military contractors (PMCs). Outsourcing Security examines the impact that bureaucratic controls and the increasing permissiveness of security environments have had on the U.S. military's growing use of PMCs during the late twentieth and early twenty-first centuries. Bruce E. Stanley examines the relationship between the rise of the private security industry and five potential explanatory variables tied to supply-and-demand theory in six historical cases, including Operation Desert Storm in 1991, the U.S. intervention in Bosnia in 1995, and Operation Iraqi Freedom in 2003. Outsourcing Security is the only work that moves beyond a descriptive account of the rise of PMCs to lay out a precise theory explaining the phenomenon and providing a framework for those considering PMCs in future global interaction.